2019
DOI: 10.4018/ijsesd.2019010104
|View full text |Cite
|
Sign up to set email alerts
|

Peri-Urban National Parks as Green Spaces for Recreation

Abstract: Little is known regarding the significance for local people of peri-urban national parks as recreational areas. The main goal of the present article is to evaluate the social impact and importance of peri-urban parks for visitors as a green space for outdoor recreation. For this investigation on-site, face-to-face interviews were conducted. The main reason for visiting NP are: “to be near to nature” (64.71%), “to practice sport” (58.09%) and “relaxing” (43.38%). Spending time in NP is considered by most interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
(4 reference statements)
1
13
0
Order By: Relevance
“…According to Centers for Disease Control and Prevention, green spaces are "open, undeveloped land with natural vegetation" and include parks, forests, playing fields, and river corridors, for example. Forests close to urban areas provide people with opportunities for recreation [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…According to Centers for Disease Control and Prevention, green spaces are "open, undeveloped land with natural vegetation" and include parks, forests, playing fields, and river corridors, for example. Forests close to urban areas provide people with opportunities for recreation [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Nature Park Shumen Plateau (NP) provides important ecosystem services to local residents. Our previous findings illustrate great social benefits of park as a green space for outdoor recreation [1]. Such green areas are perceived as "clean of pollution", but several studies revealed that they can be affected by accumulation of harmful compounds [2], [3].…”
Section: Introductionmentioning
confidence: 53%
“…It is important to have enough quality green spaces within urban and peri-urban areas (Li et al, 2005;Szulczewska et al, 2014). According our results in first part of this survey two main motivations of people to visit Nature Park are to be near to nature and to practice sport (Koynova et al, 2019 (Koynova, 2018). The park quality is considering factor that contribute to park visitation.…”
Section: Resultsmentioning
confidence: 89%
“…The demographic features of the respondents were reported and discussed in detail in the first part of this study (Koynova et al, 2019). The majority of NP visitors represent a consistent group of inhabitants of the city of Shumen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation